2020
DOI: 10.21203/rs.3.rs-100397/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ORF3a mediated-incomplete autophagy facilitates SARS-CoV-2 replication

Abstract: SARS-CoV-2 is the causative agent for the COVID-19 pandemic and there is an urgent need to understand the cellular response to SARS-CoV-2 infection. Beclin-1 is an essential scaffold autophagy protein that forms two distinct subcomplexes with modulators Atg14 and UVRAG, responsible for autophagosome formation and maturation, respectively. In the present study, we found that SARS-CoV-2 infection triggers an incomplete autophagy response, elevated autophagosome formation but impaired autophagosome maturation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…Careful analysis of LC3-positive DMVs revealed that only the endogenous non-lipidated LC3-I associates with MHV-induced DMVs, and while the LC3 lipidation machinery was dispensable for MHV replication, decreased LC3 impaired MHV replication ( Reggiori et al, 2010 ). Consistent with viral RO assembly being facilitated by autophagosome formation, but not lysosomal targeting and fusion, a recent study reported an incomplete autophagy response to SARS-CoV-2 infection ( Qu et al, 2020 ). Expression of SARS-CoV-2, but not SARS-CoV, ORF3a, was sufficient to trigger incomplete autophagy, where autophagosome formation is increased, but maturation impaired.…”
Section: Dmv Biogenesismentioning
confidence: 78%
“…Careful analysis of LC3-positive DMVs revealed that only the endogenous non-lipidated LC3-I associates with MHV-induced DMVs, and while the LC3 lipidation machinery was dispensable for MHV replication, decreased LC3 impaired MHV replication ( Reggiori et al, 2010 ). Consistent with viral RO assembly being facilitated by autophagosome formation, but not lysosomal targeting and fusion, a recent study reported an incomplete autophagy response to SARS-CoV-2 infection ( Qu et al, 2020 ). Expression of SARS-CoV-2, but not SARS-CoV, ORF3a, was sufficient to trigger incomplete autophagy, where autophagosome formation is increased, but maturation impaired.…”
Section: Dmv Biogenesismentioning
confidence: 78%
“…ORF, open reading frame; PI3KC3-C1, class â…˘ phosphatidylinositol 3-kinase complex â… ; PLpro, papain protease. [ 51,52]…”
Section: Discussionmentioning
confidence: 99%
“… NCI-H1299 /Vero FM cells AMPK/MTOR and AKT1/SKP2 signalling pathways Inhibit autophagy [ 50 ] SARS-CoV-2 ORF3a HEK293T /HeLa cells HOPS component VPS39 or autophagy regulator UVRAG; Lysosome damage Block autolysosome formation; Impair lysosomal function. [ 51 , 52 ] …”
Section: Coronavirus Infections and Autophagymentioning
confidence: 99%
See 2 more Smart Citations